Leading names in Education: The pedagogy of the Society of Jesus (Journal of Parents and Teachers, 2012)
The author explains how it works the Society of Jesus , its history and how its success has led to the implementation of the system in other schools. It is a journey on the methodology used in schools and how to teach to puoils there.
Keywords: The Society of Jesus; Education Department; experience; history of education; education